«Belleza cruel» (1958) by Ángela Figuera: A Literary Bridge Between Exiled and Inner Exiled of the Spanish Diaspora (Castilla. Estudios de Literatura, 2021)
This essay presents an exhaustive study of the particular process of editing and distribution of the book of poems Belleza cruel (1958) by Ángela Figuera (Bilbao, 1902 – Madrid, 1984) in relation to the exodus that marked the history of Spain during the twentieth century, a consequence, in turn, of the Spanish Civil War. Although most of Ángela Figuera’s literary production was published in Spain, her book Belleza cruel was published in Mexico thanks to the “Nueva España” award given by the Union of Spanish Intellectuals. The reason was twofold: to avoid censorship and to establish contact with Spanish intellectuals in exile. In short, this article presents this book as the result of a wide and polyhedral phenomenon of cultural diaspora.
Keywords: Ángela Figuera; Belleza cruel; Contemporary Spanish poetry; exile; Union of Spanish Intelectuals in México